Scaffolding: Meaningful Sequences during the Training Phase of a Learning Potential Test?. (8th May 2012) - van der Aalsvoort, Geerdina M.; van Loo, Floor; van Geert, Paul
Abstract : This study aimed at revealing scaffolding sequences of behavior during the training phase of a learning potential test. Involved were two conditions of four children with learning gains and four children without learning gains after the training phase of the subtest Classification of the Application of Cognitive Functions Scales. This subtest included three tasks: classification of color, form, and size. A dynamic system approach was used to describe the existence of four types of scaffolding that supposedly underlie the training phase. A microgenetic data analysis of the videotapes allowed coding of the behaviors of the training phase from the children and the diagnostician. Four sequences of scaffolding were defined, asking for attention of the child and giving attention as a child, asking for understanding of the child and responding to the diagnostician as a child; giving feedback to the child and responding to the feedback of the child, and offering strategies to the child and using strategies as a child. The results revealed no significant differences in the number of sequences between the conditions. Changes, however, were exposed in the relative frequency of each type of scaffolding from subtask 1 to 3. Moreover, the hierarchy of frequency of sequences differed between the conditions. The description of the findings of a boy from each condition in frequency per sequence, rainbow plot, and representative transcript revealed emergence of sequences over time. The findings are discussed with regard to theoretical reflections and methodological issues.